Sosialisasi Mitigasi Gempa Berbasis Keluarga: Meningkatkan Peran Ibu-ibu Warga Kalurahan Tegaltirto dalam Kesiapsiagaan Bencana - Novadli, Azri; Rita Mulyandari; Fithart Salman Fathrizky (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Indonesia, located within the Pacific Ring of Fire, is highly vulnerable to earthquakes. This disaster risk is exacerbated by the low level of community preparedness, particularly in Tegaltirto Village, where the majority of residents work as farmers, laborers, or livestock breeders with limited education and disaster knowledge. A community service program conducted by the Civil Engineering Department of Universitas Madani aimed to empower women, especially mothers, as the frontline of family-based earthquake mitigation. The program was implemented through socialization, demonstrations, hands-on practice, and post-activity mentoring. Initial surveys revealed that 85% of participants had minimal knowledge of practical earthquake mitigation measures. After the program, post-test scores increased by 72%, indicating a significant improvement in both theoretical understanding and practical skills, particularly in preparing emergency kits. These findings highlight that participatory methods combined with practical learning effectively promote transformative learning and enhance community preparedness. Therefore, similar training programs should be carried out sustainably with support from local authorities and community leaders to foster a culture of disaster preparedness at the family level.